Analisis Kebutuhan dan Desain E-LKPD Matematika Berbasis Pendekatan Concrete Pictorial Abstract (CPA) Terintegrasi Kearifan Lokal pada Materi Pecahan Kelas III Sekolah Dasar - Ni Komang Sri Wahyu Tistari; I Gede Suwindia; Ni Nyoman Kurnia Wati (Jayapangus Press, 2026)
Fraction learning in elementary schools continues to show low levels of students’ conceptual understanding due to the dominance of procedural instruction and the limited availability of learning media that facilitate concrete and visual representations. This study aims to map the learning needs of fraction instruction and to formulate an E-LKPD design that systematically integrates the Concrete–Pictorial–Abstract (CPA) approach with local wisdom for third-grade elementary school students. The study employed a research and development method using descriptive qualitative and quantitative approaches, limited to the needs analysis and design stages. Data were collected from third-grade teachers and students in Cluster III, Kerambitan District, through classroom observations, semi-structured interviews, and document analysis, and were analyzed descriptively. The findings indicate that students’ low conceptual understanding of fractions is associated with limited visualization, insufficient concrete learning experiences, and the absence of local cultural contexts in instructional practices. The novelty of this study lies in the formulation of an E-LKPD design that combines the CPA representational sequence with local cultural contexts within a structured digital learning framework. Theoretically, the findings reinforce the relevance of contextualized representational approaches in elementary mathematics learning, while practically, the proposed design provides teachers with a reference for developing more meaningful, interactive, and context-based fraction instruction.